2022
DOI: 10.1097/iio.0000000000000406
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Disease Prevention and Management in Traumatic Open Globe Injuries

Abstract: Table 1). Rates of endophthalmitis tend to be higher with a history of retained intraocular foreign body (IOFB) 16,17,20,26 (Table 1). Risk FactorsThe risk factors for developing endophthalmitis have been well studied. The most commonly cited risk factors include delayed primary wound closure (typically defined as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
(250 reference statements)
0
1
0
Order By: Relevance
“…For example, Meng and Yan 10 and Williams et al 16 concluded that endophthalmitis is a factor indicating poor visual prognosis. Notably, wound closure within 24 hours of injury has been shown to reduce the risk of endophthalmitis, 29 a finding that has resulted in a standard of care to operate on OGIs within 24 hours of initial injury whenever feasible. There seems to be a consensus that nondelayed wound closure and comprehensive prophylactic antibiotic treatment at the time of injury may improve final VA following OGI 15 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Meng and Yan 10 and Williams et al 16 concluded that endophthalmitis is a factor indicating poor visual prognosis. Notably, wound closure within 24 hours of injury has been shown to reduce the risk of endophthalmitis, 29 a finding that has resulted in a standard of care to operate on OGIs within 24 hours of initial injury whenever feasible. There seems to be a consensus that nondelayed wound closure and comprehensive prophylactic antibiotic treatment at the time of injury may improve final VA following OGI 15 .…”
Section: Introductionmentioning
confidence: 99%